2016
DOI: 10.1080/07448481.2016.1270949
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national comparisons of college students' attitudes toward diet/fitness apps on smartphones

Abstract: Findings from the cross-national comparisons were helpful for thoroughly understanding the contextualized mechanisms involved in the adoption of diet/fitness apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Relying on self-report to gather hookah use data may raise concerns related to recall and response bias. Finally, similar to previous research on hookah smoking (Doran, Godfrey, & Myers, 2015; Jones & Cunningham-Williams, 2016), we defined current use as any use in past 30 days, which may limit the comparability of the study findings with other studies (Agaku, et al, 2014) that define current use differently.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on self-report to gather hookah use data may raise concerns related to recall and response bias. Finally, similar to previous research on hookah smoking (Doran, Godfrey, & Myers, 2015; Jones & Cunningham-Williams, 2016), we defined current use as any use in past 30 days, which may limit the comparability of the study findings with other studies (Agaku, et al, 2014) that define current use differently.…”
Section: Discussionmentioning
confidence: 99%
“…To test quality, risk of bias analysis of the 19 studies evaluated in the research showed that only three studies had a high score of 15 points or more out of 20 total [1,45,51], most studies (n = 14) had a mean score between 10 and 15 points and only two studies had a score below 10 points [52,53]. It should be noted that none of the studies analyzed carried out a calculation of the sampling required for the generalization of the results, which could be due to the fact that all the studies carried out a selection of the sample for convenience within a certain population.…”
Section: Analysis Of the Risk Of Bias In Studiesmentioning
confidence: 99%
“…Li, Liu, Ma and Zhang [46] sampled subjects over 25 years of age, while Huang and Ren [60] and Mohammadi and Isanejad [57] were at least 30 years old. Regarding the type of App evaluated, six studies evaluated the intention to use diet and fitness applications [30,44,51,52,55,59], another five studies evaluated sports information Apps [42,43,53,57,62], two studies measured the intention of fans to use the sports team app [1,45], health and fitness app [56,61], or fitness [58,60] and one study evaluated a social fitness-tracking app [63] and mHealth related to promote physical activity [54]. The most widely used theory for the design and use of the mobile sports app intent of use assessment instrument was TAM (n = 10).…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the model has been influenced by other external variables, such as social norms [ 49 ], health awareness [ 54 ], commitment to or participation in sport [ 50 ], and entertainment [ 55 ], and sociodemographic variables, such as gender, age, or frequency of use [ 53 ]. In this way, research with TAM has determined that PEU and PU are influenced by different external variables.…”
Section: Literature Reviewmentioning
confidence: 99%